Full‐body skin examination in screening for cutaneous malignancy: A focus on concealed sites and the practices of international dermatologists - James P. Pham; Nicholas Allen; Phoebe Star; Anne Cust; Pascale Guitera; Ashfaq A. Marghoob; John Paoli; Iris Zalaudek; Annika Smith (Wiley, 2024)
Abstract Background Full‐body skin examination (FSE) is fundamental to the diagnosis of cutaneous malignancy but may not always include concealed site examination (CSE). Objectives To determine the approach of international dermatologists to CSE during FSE and examine influencing factors, barriers and attitudes toward CSE. Methods Members of the International Dermoscopy Society were surveyed using an online 12‐question survey disseminated via email. Results There were 706 completed responses among 1249 unique clicks to the survey, representing a completion rate of 56.5%. Fifty‐four percent of respondents reported always examining the breasts, while 52.8%, 18.8%, and 11.8% always examined the scalp, oral, and anogenital mucosa, respectively. The most frequent reason for examining concealed sites was patient concern, whilst common reasons for not examining concealed sites included low incidence of pathology and concern regarding allegations of sexual misconduct. Conclusions Our findings allude to the need for international consensus guidelines regarding the conduct and inclusion of concealed or sensitive sites in routine FSE. This is essential to define clinician responsibilities, inform patient expectations of care, and thereby mitigate potential medicolegal repercussions.